2017
DOI: 10.20944/preprints201702.0036.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanoparticle-Mediated Drug Delivery System for Pulmonary Arterial Hypertension

Abstract: Nanoparticles have been used as a novel drug delivery system. Drug-incorporated nanoparticles for local delivery might optimize the efficacy and minimize the side effects of drugs. The efficacy and safety of intratracheal administration of prostacyclin analog (beraprost)-incorporated nanoparticles and imatinib, a PDGF-receptor tyrosine kinase inhibitor, -incorporated nanoparticles in Sugen-hypoxia-normoxia or monocrotaline rat models of PAH and in human PAH-pulmonary arterial smooth muscle cells have been repo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…However, many nanoformulations, still in pre-clinical development show promising perspectives. Few current clinical trials of nanomedicine related to respiratory diseases have been reported, and the clinically known applications of nanocarriers are liposomes [65,126] in non-tuberculous mycobacterial lung disease and lung cancer, and PLGA in pulmonary arterial hypertension [127]. Table 1, far from being exhaustive, presents some examples to illustrate the potential of nano-delivery systems loaded with different agents (antibiotics, anti-inflammatory agents…) for the potential treatment of various respiratory diseases.…”
Section: Concrete Examples Of Applicationsmentioning
confidence: 99%
“…However, many nanoformulations, still in pre-clinical development show promising perspectives. Few current clinical trials of nanomedicine related to respiratory diseases have been reported, and the clinically known applications of nanocarriers are liposomes [65,126] in non-tuberculous mycobacterial lung disease and lung cancer, and PLGA in pulmonary arterial hypertension [127]. Table 1, far from being exhaustive, presents some examples to illustrate the potential of nano-delivery systems loaded with different agents (antibiotics, anti-inflammatory agents…) for the potential treatment of various respiratory diseases.…”
Section: Concrete Examples Of Applicationsmentioning
confidence: 99%
“…In the past 20 years, several drugs have become available for PAH treatment, including prostacyclin (prostaglandin I 2 ), endothelin receptor antagonists (ERAs), phosphodiesterase type-5 inhibitors (PDE-5i), and a soluble guanylate cyclase stimulator. However, their full therapeutic effects are hampered by nonadherence and side effects, and PAH is still an aggressive and fatal disorder for many patients (Nakamura et al 2017).…”
Section: Pulmonary Artery Hypertensionmentioning
confidence: 99%
“…A phase I, investigator-initiated clinical trial to test the efficacy of PLGA NP-mediated delivery of pitavastatin (UMIN000014940) has recently been completed (Nakamura et al 2017). Future clinical trials may prove the safety and efficacy of a nano-drug delivery system for PAH.…”
Section: Clinical Trials Of Nanotherapymentioning
confidence: 99%
“…Briefly, in the process of developing nanomedicine for the treatment of respiratory diseases, it is necessary to systematically explore the interaction between the nanomedicine and the respiratory system, including in vitro and in vivo detection methods to measure the genotoxicity, cytotoxicity and tissue toxicity of the drug ( 119 ), in order to thoroughly examine the safety, tolerability and therapeutic effect of NPs in treatment. Although some preclinical studies have shown promising application prospects, the current clinical trials of nanomedicine related to respiratory diseases remain limited, and the clinically known applications of nanocarriers are liposomes ( 48 , 49 ) in nontuberculous mycobacterial lung disease and lung cancer, and PLGA in pulmonary arterial hypertension ( 120 ).…”
Section: Application Of Nps In Respiratory Systemsmentioning
confidence: 99%